Simulasi Pengunaan Dongeng “Bubu dan Biji Ajaib” kepada Petugas Lapangan Terkait Kepatuhan Minum Obat pada Anak dengan HIV/AIDS - Sri Handayani; Rifda Wahyuni; Gusliani Eka Putri (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
The incidence of HIV/AIDS in children continues to rise, mainly due to mother-to-child transmission. Although antiretroviral (ARV) therapy effectively reduces mortality, adherence among children remains low. This community service activity aimed to improve field officers’ pedagogical skills in educating children on ARV adherence through storytelling. The activity was conducted on June 12, 2025, at Yayasan Akbar in Padang City, involving 10 field officers. The method included training on storytelling techniques using the book "Bubu dan Biji Ajaib" (Bubu and the Magic Seed) and hand puppets, supported by pre-test and post-test evaluations. Results showed a significant increase in storytelling skills, with an average score improvement of 22.41 points after the intervention. The most notable improvements were in eye contact, creativity, facial expressions, and mastery of hand puppet use. In conclusion, the storytelling simulation effectively enhanced participants’ ability to deliver educational messages to children and should be integrated into child health education programs, especially for children living with HIV/AIDS.